THE ROLE OF INTERNATIONAL ORGANIZATIONS IN THE STIMULATION SYSTEM OF THE ALTERNATIVE ENERGETICS DEVELOPMENT - Shulga, I.V.; Haraschuk, V.M.; Kalayanov, D.P. (Scientific Journal of Pedagogy and Economics, 2020)
The article focuses on the rapid increase in the role of the system of stimulation tools in the alternative energetics development in a context of the process of comprehensive greening of the modern world economy. The problems of the category determination of "stimulation" are reviewed both in modern legal science in general and in the field of international legal relations related to the development of alternative energetics. The incentive means of the development of alternative energetics, used at the domestic level, which are most widely used at the present stage of social development, are clarified. The main content of the work touches upon urgent problems of the role of international organizations in the stimulation system of the alternative energetics development. The importance of their participation in ensuring the sustainable development of the industry under study is substantiated, their role and function in the stimulation system of the alternative energetics are determined, and a classification of their activities is proposed. The tasks of governmental and non-governmental international institutions are analyzed in terms of the proposed classification; the examples are given from the practical implementation of tasks by several major international organizations. The options are proposed for improving the present model for the participation of international organizations with the stimulation system of the alternative energetics development. The focus is made on the problem of the states’ international responsibility for non-compliance with international treaties and the problem of priority correlation of international interest and state sovereignty in matters of reducing CO2 emissions into the atmosphere. It is concluded that there is a current trend of reorienting the activities of international organi-zations towards differentiation. It is stated that the programs and recommendations of international organizations are developed directly for particular states, taking into account their geography and economic status when choosing types and methods for the alternative energetics development.